2008
DOI: 10.1124/jpet.108.141366
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Pharmacokinetics of (±)3,4-Methylenedioxymethamphetamine (MDMA, “Ecstasy”) and Its Major Metabolites in Squirrel Monkeys at Plasma Concentrations of MDMA That Develop After Typical Psychoactive Doses

Abstract: At certain doses, the psychoactive drug (Ϯ)3,4-methylenedioxymethamphetamine (MDMA, "Ecstasy") destroys brain serotonin axon terminals. By causing increases in plasma MDMA concentrations that exceed those predicted by the increase in dose, nonlinear pharmacokinetics has the potential to narrow the range between safe and neurotoxic doses of MDMA. The present study sought to determine whether the pharmacokinetics of MDMA in nonhuman primates are nonlinear and, if they are, to identify plasma concentrations of MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 26 publications
4
39
0
1
Order By: Relevance
“…The pattern of responding after administration of 1.0 mg/kg MDPV was quite similar, and it seems likely that a higher dose of MDPV would look very similar indeed to what we have previously seen with 3.0 mg/ kg MDMA. We have also reported that cumulative doses of MDMA lead to higher concentrations of MDMA in plasma, 3,4-Methylenedioxypyrovalerone in mice WE Fantegrossi et al as compared with administration of an equivalent bolus dose, revealing that, consistent with previous studies in rats (Chu et al, 1996), squirrel monkeys (Mechan et al, 2006;Mueller et al, 2008), and humans (de la Torre et al, 2000), metabolism is also decreased when the dose is administered cumulatively in the mouse . Analogous studies have not yet been performed with MDPV, but it is possible that this compound also displays nonlinear pharmacokinetics, which may explain the apparent potency differences here observed when the drug was administered cumulatively, vs when it was given as a single bolus dose.…”
Section: 4-methylenedioxypyrovalerone In Micesupporting
confidence: 78%
“…The pattern of responding after administration of 1.0 mg/kg MDPV was quite similar, and it seems likely that a higher dose of MDPV would look very similar indeed to what we have previously seen with 3.0 mg/ kg MDMA. We have also reported that cumulative doses of MDMA lead to higher concentrations of MDMA in plasma, 3,4-Methylenedioxypyrovalerone in mice WE Fantegrossi et al as compared with administration of an equivalent bolus dose, revealing that, consistent with previous studies in rats (Chu et al, 1996), squirrel monkeys (Mechan et al, 2006;Mueller et al, 2008), and humans (de la Torre et al, 2000), metabolism is also decreased when the dose is administered cumulatively in the mouse . Analogous studies have not yet been performed with MDPV, but it is possible that this compound also displays nonlinear pharmacokinetics, which may explain the apparent potency differences here observed when the drug was administered cumulatively, vs when it was given as a single bolus dose.…”
Section: 4-methylenedioxypyrovalerone In Micesupporting
confidence: 78%
“…There are discrepancies in whether MDMA follows nonlinear pharmacokinetics in rats, as documented in humans, monkeys, and mice (de la Torre et al, 2000;Kolbrich et al, 2008b;Mueller et al, 2008;Scheidweiler et al, 2011). Green et al (2009Green et al ( , 2012 compared literature values for plasma MDMA concentrations following highdose MDMA administration in rats (i.e., 5-20 mg/kg via i.p., s.c., or po routes) to those produced by low-dose administration in humans (i.e., 0.5-2 mg/kg po).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest a non-linear pharmacokinetic response to MDMA in human, monkey and rat (Kolbrich et al, 2008;de la Torre et al, 2000;Chu et al, 1996;Mueller et al, 2008). There have been a few reports regarding the physical or pharmacological effects resulting from interactions caused by MDMA tablet intake or multi-drug abuse.…”
Section: Pharmacodynamic Effects Of Mdma On Dopamine and 5-ht Levels mentioning
confidence: 99%